A Review of Attachment and its Relationship to the Working Alliance - Kietaibl, Carin M. (Canadian Journal of Counselling and Psychotherapy, 2012)
Attachment theorists propose that attachment styles affect the development of relationships inside and outside of therapy. By integrating attachment theory into their work with clients, therapists may strengthen the working alliance and lower the risk of clients prematurely ending therapy. Attachment theory is reviewed, and methods of integrating it into counselling practice are discussed. Daly and Mallinckrodt’s (2009) model of adapting therapeutic distance to establish safety in the therapy relationship is presented. Also reviewed is how therapists can integrate client culture into the adjustment of therapeutic distance.